2018
DOI: 10.1039/c8nr03074j
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-targeted photodynamic and gene dual therapy for effectively inhibiting triple negative breast cancer by cationic porphyrin lipid microbubbles loaded with HIF1α-siRNA

Abstract: Enhanced PDT and siRNA transfection effect of siRNA@CpMBs were successfully achieved by in situ conversion of MBs to NPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Another exciting development in the realm of enhanced US‐guided PDT came from the research of Sun et al ., in which they combined US‐targeted PDT with gene therapy to treat triple‐negative breast cancer. They achieved this goal by using cationic porphyrin lipid microbubbles loaded with HIF1alpha‐siRNA, providing a therapeutic with both enhanced contrast and the added element of interfering with tumor function on the level of the transcriptome . The complexities of gene expression provide a multitude of therapeutic targets, from transcription factors (TF) and miRNA‐mediated transcriptional up‐ or downregulation , to cis‐ and transchromosomal long noncoding RNA (lncRNA) bridges, , all of which contribute to the proteomic profiles and organellar architecture of a cell .…”
Section: Theranostic Nanomaterials For Image‐guided Pdtmentioning
confidence: 99%
“…Another exciting development in the realm of enhanced US‐guided PDT came from the research of Sun et al ., in which they combined US‐targeted PDT with gene therapy to treat triple‐negative breast cancer. They achieved this goal by using cationic porphyrin lipid microbubbles loaded with HIF1alpha‐siRNA, providing a therapeutic with both enhanced contrast and the added element of interfering with tumor function on the level of the transcriptome . The complexities of gene expression provide a multitude of therapeutic targets, from transcription factors (TF) and miRNA‐mediated transcriptional up‐ or downregulation , to cis‐ and transchromosomal long noncoding RNA (lncRNA) bridges, , all of which contribute to the proteomic profiles and organellar architecture of a cell .…”
Section: Theranostic Nanomaterials For Image‐guided Pdtmentioning
confidence: 99%
“…Sun et al [180] designed a multifunctional compound (siHIF@CpMB) constituted by cationic porphyrin lipip microbubbles (CpMBs), elaborated from cationic porphyrin lipip NPs, and loading HIF-1α siRNA (siHIF) on the surface by electronic adsorption. In vitro in MDA-MB-231 cells, the authors observed an efficient release of siHIF after ultrasound exposure (1.03 MHz, 50 % duty, 1 W•cm −2 , 1 min) and production of 1 O 2 after irradiation (650 nm, 200 mW•cm −2 , 10 min).…”
Section: Hif-1α Inhibitorsmentioning
confidence: 99%
“…In another recent study by Liang and Wang et al., HIF‐1α siRNA was loaded into a cationic porphyrin‐grafted lipid microbubble. The microbubbles can be efficiently converted into nanoparticles in situ under ultrasound treatment, which facilitates the accumulation of photosensitizer and siRNA at the tumor site through the cavitation effect 34 . HIF‐1α siRNA in this system can downregulate the hypoxia‐induced HIF‐1α level and enhance the PDT against triple‐negative breast cancer.…”
Section: Ameliorating Tumor Hypoxiamentioning
confidence: 99%